Research progress on the treatment of diabetic nephropathy with leech and its active ingredients - Tian, Feng; Yi, Xiang; Yang, Feifei; Chen, Yao; Zhu, Wenhui; Liu, Peng; Li, Shuju (Frontiers in Endocrinology, 2024)
Diabetic nephropathy (DN) is a major microvascular complication of diabetes and a common cause of chronic kidney disease. There is currently a lack of effective treatments for DN, and the prognosis for patients remains poor. Hirudin, one of the primary active components derived from leeches, demonstrates anti-coagulant, anti-fibrotic, anti-thrombotic, and anti-inflammatory properties, exhibiting significant protective effects on the kidneys. In recent years, there has been a surge of interest in studying the potential benefits of hirudin, especially in its role in the management of DN. This article delves into the mechanisms by which hirudin contributes to the treatment of DN and its clinical efficacy.